Development of 3D BEM code for Computation of a Transformer Winding's Capacitance Matrix. (2017) - Trkulja, Bojan; Drandić, Ana; Štih, Željko
Abstract: In this paper, a method for computation of capacitance matrix for a transformer geometry is presented. Computation is based on boundary elements methods and point-matching. Unknown charge distribution on a triangular surface mesh of a winding is modeled with constant surface charge density over a triangle. Capacitance matrix is then obtained from known potentials in nodes of the system. Computation of relevant capacitances is benchmarked using the professional finite element method (FEM) based software.